EFFECTS OF PERIODS AND CONDITIONS OF STRATIFICATION AND SOAKING IN HOT WATER ON SEED GERMINATION AND SEEDLING GROWTH OF Melia azedarach L. - Riyadh S. AL-Khaffaf; Yaqoob Shamaon Lazar (Mesopotamia Journal of Agriculture)
This study was carried out in the greenhouse/forestry department /college of agriculture and forestry, to study the effects of stratification period, hot water degrees and stratification degrees on seed germination of Melia azedarach seedling growth. The results showed the superiority of 45 days of stratification in all the studied characters (germination energy, germination percentage, seedling length, seedling diameter and number of leaves). The resulted averages were 37.42%, 59.24%, 75.77cm, 9.78mm, 114 leaf respectively. Among the hot water degrees the superiority in all the characters was in the case of 50°C and gave the averages 35.90%, 56.02, 63.89 cm, 8.02mm, 97.14 leaf respectively. Due to stratification degrees; 4°C showed superiority in seedling length character only and gave an average of 57.53 cm. Also the interaction among stratification in the incubator for 45 days and soaking in 50°C hot water were superior in germination energy and germination percentage characters. Furthermore the interaction of stratification for 45 days in refrigerator and soaking degree 50°C was superior in the characters of seedling length ,seedling diameter and number of leaves.